Untimely destruction: pestilence, war, and accumulation in the long run - Bell, Clive; Gersbach, Hans; Komarov, Evgenij (Macroeconomic dynamics, 2024)
This paper analyses the effects of disease and war on the accumulation of human and physical capital. We employ an overlapping generation framework in which young adults, motivated by old-age provision and possibly altruism, make decisions about investments in schooling and capital. A poverty trap exists for a wide range of constant war losses and premature adult mortality. If parents are altruistic and the sub-utility function for own consumption is more concave than that for their evaluation of their children’s full income in adulthood, the only possible steady-state growth path involves full education. Otherwise, steady-state paths with incompletely educated children may exist. When mortality and destruction rates are stochastic, the initial boundary conditions and agents’ beliefs have a strong influence on the paths generated by a sequence of shocks. Calibrating the model to Kenya, simulations for stochastic settings yield the finding that a trap exists and is always avoided, but the chances of a slow recovery are substantial.
Gesehen am 11.03.2024